46 MARKPAP® TEST, A POTENTIAL METHOD FOR MONITORING THE SUCCESS OF HUMAN PAPILLOMAVIRUS VACCINATION. (1st March 2006) - Markovic, N.; Markovic, O.
Abstract : Introduction: The MarkPap biomarker, the specific isoenzyme configuration of cervical acid phosphatase, was described in 1999 (<www.bioscicon.com >). It labels abnormal cervical cells, such as dysplastic, HPV-infected, and malignant cells. Visualized with the MarkPap test as a red pigment on the Papanicolaou bluish background, the biomarker increases the visibility of abnormal cells and serves as their locator. Normal squamous epithelial cells are always negative. In case of HPV, the marker labels infected cells providing in the same time information about their morphological changes. Methods: The MarkPap test is suited for both conventional smears and for liquid-based Pap. Specimens can be processed in small laboratories with the MarkPap Test manual mode, in large laboratories with automatic mode, or MarkPap Digital telecytopathology can be applied if the processing of samples and their evaluation can not be done at one site (<www.bioscicon.markpapproducts.html >). MarkPap Digital is expected to become a new low-cost mass cervical cancer screening tool. Results and Conclusion: In our studies, we found that MarkPap biomarker positivity and morphological changes (typically seen in HPV-infected patients with koilocytosis) are independent phenomena. The successful clinical trials with HPV vaccines will open another broad application for MarkPap technology. Since MarkPap could detect HPV-infected cells together with cytological singes of abnormality (the actual reaction of the cell, not only the presence of the virus), this simple and low-cost test may be applied for large-scale monitoring of the success of HPV vaccination around the world. It may help answer questions of duration of the protection under repeated new infections, the need for reimmunization, presence of other low-risk HPV strains that produce reaction of the cell, virus transformation, and many others. The authors greatly appreciate the continuous support of Dr. Charlie Grudzinskas, NDA Partners, LLC, Annapolis, MD.